Different coordination modes of bis(imine-ridine) and bis(quinaldine) ligands - Prema, Dipesh (Kansas State University, 2007)
2-Formylbenzoquinoline and a selection of novel chiral bis(pyridine-imine) and bis-amide ligands derived from (1R,2R)-cyclohexanediamine and (R)-[1,1’-binaphthalene]-2,2’-diamine have been synthesized and thoroughly characterized. Subsequently, their coordination chemistry has been investigated. Metallation with Zn(II), Ni(II) and Fe(II) has resulted in the formation of a series of helical complexes, some of which exhibit unusual coordination modes. Bis(imine-pyridine) ligands were found to form dinuclear complexes upon reaction with ZnCl2. In one case, the use of Zn(CF3SO3)2 resulted in the formation a single stranded monohelix, after the ligand had undergone a reduction at one imine bond. The use of NiI2 as the metal salt resulted in the formation of penta-coordinate complexes with N3-coordination and helical dinuclear complexes with bridging iodo ligands. Ni(CF3SO3)2 was also used, this resulted in the formation of a double stranded mononuclear complex. The ligand, in this case was hydrolyzed to yield a tridentate ligand, subsequently two of these new ligands coordinate to one metal center to form the complex. Bis-amide ligands were reacted with FeCl2 and Fe(CF3SO3)2 to form complexes with various different colors. In all but one case, several attempts to structurally characterize the Fe(II) complexes were unsuccessful. Suitable crystals of this complex revealed a double stranded helicate complex that coordinates through carbonyl oxygens rather than amide nitrogens. The work described herein, is an account of the synthesis, characterization and study of a new family of tetradentate nitrogen donor ligands and their respective transition metal complexes.
Keywords: Inorganic; Coordination Chemistry; Chemistry; Organic; Ligand synthesis; Catalysis; Chemistry, Inorganic (0488)